SISTEM PENDIDIKAN DI NEGARA MAJU AMERIKA SERIKAT - Abdul Wahab Syakhrani; Ahmad Maulani; Ahmad Saubari; Muhammad Yusuf; Muhammad Ilham (CV. ADIBA AISHA AMIRA, 2022)
The education system in the United States is almost similar to that in Indonesia, consisting of 3 layers of government, namely federal or central government, provincial or state government called state government and the third city or district government called local government. In the United States education system, there are several patterns of educational structure, both at the elementary and secondary levels, as well as at the higher education level.